2019 Presidential Election: Between Political Contestation and Competition Triggering Nation Split - Huda, Khoiril; Fadhlika, Zulfa ‘Azzah (Law Research Review Quarterly, 2018)
In elections there are political contestations that encourage the candidates for leaders to make efforts to win the general election. This has caused different reactions in the community regarding their views on the efforts made by the contestants. Tightness between supporters of the two candidate pairs causes the presidential election in 2019 to have its own uniqueness compared to previous presidential elections. This presidential election is a rematch of competition 4 years ago in 2014. There are interesting things that need to be examined further about the phenomena that occur prior to the 2019 presidential election. One of the things in question is the competition between two camps of candidate pairs . The competition between the two has caused various reactions among the people. In fact, differences in principles and perspectives make patterns emerge as if there is competition to seep into the strata of society. So the things about triggering divisions in the community in welcoming the 2019 presidential election contestation are very important to study in order to maintain the integrity of the nation because Indonesia is a country that highly values ​​pluralism and is prone to division. The object of research that will be examined is the attitude of the community towards the 2019 Presidential Election using descriptive qualitative research methods.